Utilização de operadores integradores na cadeia de suprimentos e logística da indústria de petróleo e gás no Brasil: uma proposta de valor dos operadores para os gestores da indústria - Balla, Bruno Rodrigues (2016)
The main objective of this study was to investigate which value attributes a fourth party logistics (4PL) operator must offer to potential oil & gas clients, in order to properly serve the managing worries and orders commonly present in such industry operational routine. With this intent and based on the theoretical framework, a value proposal was elaborated for these operators, allowing us to verify its consistency within the referred market. The proposal was both based on the market’s supply and logistics chain differentiation principles, such as flow integration or operational and management capacities development, as on the main characteristics of the 4PL operator, related to their capacity to bring knowledge and experience to the operation, to provide operational flow through technology and to manage their clients’ network operations. 6 (six) semi structured interviews were applied to operations’ managers of major companies operating in this sector in Brazil. The interviews outcomes are not entirely opposed to the use of an operator like these within the industry’s companies. It has called attention, however, to topics with which these operators should be worried about, such as: a possible cost increase, the level of service required by the business, the operational issues attached to the uncertainty over demand & operational risks, the strict trust usually attributed to suppliers and the maturity of the market itself, whether concerning contractors or available suppliers.